Examining the effects of green human resource management practices, green psychological climate, and organizational pride on employees’ voluntary pro-environmental behavior - Zafar, Hina; Suseno, Yuliani (SAGE Publications, 2024)
Drawing on social exchange theory and social identity theory, we examined a sequential mediation process linking green human resource management practices and employees’ voluntary pro-environmental behavior. We also considered the aspects of green psychological climate and organizational pride in the relationship between green human resource management practices and voluntary pro-environmental behavior. Through the analysis of data from 459 employees and their 109 respective managers working in Pakistan’s textile industry, we found that a green psychological climate mediates the relationship between green human resource management practices and organizational pride. We also found that green psychological climate and organizational pride sequentially mediate the relationship between green human resource management practices and employees’ voluntary pro-environmental behavior. The findings of the study provide important implications for theory and practice, as they offer insights into how organizations can effectively implement green human resource management practices and encourage their employees to engage in voluntary pro-environmental behavior. © The Author(s) 2024.